Sustaining competitive advantage in the UK's rail spares overhaul market - Fyson, Nick (2007)
The dissertation sets out to investigate how Bombardier can develop and sustain competitive advantage within the UK spares overhaul market. This is an important market to the company. Bombardier has positioned itself as a full service provider to the rail industry. Without the ability to compete in the overhaul market, it can no longer sustain this proposition. Two components and three strategic models have been selected to analyse the market and to develop strategic options. Bogies and engines have been selected because they are high value components that are central to the profitability of the business. The three models are: 1. Porter's Five Forces - Porter's model focuses upon the macro environment and the threats that it contains. 2. The Resource Based View of the Firm - The Resource model investigates the company's strengths and what it can do. 3. Co-opetition - The Co-opetition model provides a framework for how we can change the game to our advantage. The combination of these three models allows us to view the issues from different but complementary aspects. The Five Forces analysis identified potential threats such as there are a number of potential entrants to the market and few barriers to entry. The Resource analysis highlighted the capabilities that we need to sustain, specifically the ability to develop and implement Component Overhaul Instructions (COIs). The Co-opetition model generated potential solutions for adding value by differentiating the products through focusing on product quality and on-time delivery. We also saw how we could potentially change the game to our advantage by acquiring competitors and suppliers.